Association of Blood Pressure–Related Increase in Vascular Stiffness on Other Measures of Target Organ Damage in Youth. Issue 9 (28th June 2022) - Haley, Jessica E.; Woodly, Shalayna A.; Daniels, Stephen R.; Falkner, Bonita; Ferguson, Michael A.; Flynn, Joseph T.; Hanevold, Coral D.; Hooper, Stephen R.; Ingelfinger, Julie R.; Khoury, Philip R.; Lande, Marc B.; Martin, Lisa J.; et al.
Abstract : Background: Hypertension-related increased arterial stiffness predicts development of target organ damage (TOD) and cardiovascular disease. We hypothesized that blood pressure (BP)–related increased arterial stiffness is present in youth with elevated BP and is associated with TOD. Methods: Participants were stratified by systolic BP into low- (systolic BP <75th percentile, n=155), mid- (systolic BP ≥80th and <90th percentile, n=88), and high-risk BP categories (≥90th percentile, n=139), based on age-, sex- and height-specific pediatric BP cut points. Clinic BP, 24-hour ambulatory BP monitoring, anthropometrics, and laboratory data were obtained. Arterial stiffness measures included carotid-femoral pulse wave velocity and aortic stiffness. Left ventricular mass index, left ventricular systolic and diastolic function, and urine albumin/creatinine were collected. ANOVA with Bonferroni correction was used to evaluate differences in cardiovascular risk factors, pulse wave velocity, and cardiac function across groups. General linear models were used to examine factors associated with arterial stiffness and to determine whether arterial stiffness is associated with TOD after accounting for BP. Results: Pulse wave velocity increased across groups. Aortic distensibility, distensibility coefficient, and compliance were greater in low than in the mid or high group. Significant determinants of arterial stiffness were sex, age, adiposity, BP, and LDL (low-density lipoprotein) cholesterol. Pulse wave velocity and aortic compliance were significantly associated with TOD (systolic and diastolic cardiac function and urine albumin/creatinine ratio) after controlling for BP. Conclusions: Higher arterial stiffness is associated with elevated BP and TOD in youth emphasizing the need for primary prevention of cardiovascular disease.